A vueltas con la discrecionalidad administrativa (2010)
The closest possibility to the domain and subsequent control of a phenomenon, is to know. Administrative discretion is one of the unfinished items of administrative law, when they seem to run out the discussions, the issue reappears with new lights. For the dynamics of administrative activity is a source of constant re-evaluation in order to achieve an acting administration efficiently. In this paper we analyze core issues surrounding the discretion of the Administration, and are, in our view, essential to know the reason for the existence of an intitution as contentious and controversial.